ANALISIS KEGIATAN PENAMBANGAN PASIR – BATU TERHADAP EROSI, KUALITAS AIR DAN SOSIAL EKONOMI MASYARAKAT DI SEKITAR SUNGAI INDRAGIRI - - Tamrin; Zulfan Saam; Sofyan H. Siregar (LPPM Universitas Muhammadiyah Riau, 2018)
The research was done in December 2016 to March 2017 and located in Pasir Keranji Village, Pasir Penyu Districts, Indragiri Hulu Regency. The purpose of this research is analizing the impacts of sandstone mining activities against erosion in Indragiri River, quality of Indragiri River water and local socio-economic conditions. Based on the reasearch, sand-stone mining in Indragiri River causes erosion so that the river body widened and the depth of the river is shallower due to sedimentation. Other than that, quality of Indragiri River water such as brightness, turbidity, TSS, DO and BOD5 including the polluted category. This is caused by sand-stone mining activities, waste from palm factory and gold mining along the Indragiri River. Socially and economically, the sand-stone mining activities have a positive impact in improve the living standards of local communities and have a negative impact on environmental quality